The comparison of narcotics criminalization in Indonesia and The Netherlands - Fedhli Faisal; Ali Imron (Privietlab, 2025)
This article discusses the comparative punishment for drug crimes in Indonesia and the Netherlands, two countries with very different legal approaches to dealing with drug-related cases. This article's primary goal is to examine the variations in the two nations' criminal policy strategies, the types of sanctions, and the legal foundations. This study uses a comparative legal method by examining the laws, doctrines, and criminal policies in force in each country. The results show that Indonesia tends to use a repressive approach with the threat of severe criminal penalties, including the death penalty and life imprisonment, whereas the Netherlands adopts a limited decriminalization approach for certain substances, focusing on rehabilitation and harm reduction. These findings reflect the differences in criminal law philosophy between punitive and more progressive legal systems. This article recommends a re-evaluation of the effectiveness of punishment in Indonesia, taking into account a more humane and public health-based approach, such as that applied in the Netherlands